Dr. Behrooz Torkian — Deep Plane Facelift — Beverly Hills - Torkian, Behrooz (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Behrooz Torkian, practicing in Beverly Hills, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003226; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; beverly hills